Fibrotic contracture of the canine infraspinatus muscle - Devor, M.; Sørby, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Fibrotic contracture of the canine infraspinatus muscle (FCIM) is considered a rare musculotendineous disorder mainly affecting hunting dogs. After an acute onset of a painful non-weight bearing lameness, the initial pain and lameness improve over a period of one to four weeks, after which a characteristic circumducted gait abnormality develops in the forelimb. The initial injury to the infraspinatus muscle is not fully recognized or correctly interpreted in most cases, at least not with regard to its potential as a precursor of myopathy and FCIM. A mixed breed hunting dog developed an acute and extremely painful swelling of the infraspinatus muscle. The injury was easily recognized during clinical examination. The clinical signs were interpreted as an osteo-fascial compartment syndrome (OFCS) of the infraspinatus muscle. Immediate surgical decompression of the osteo-fascial compartment to prevent development of FCIM was undertaken. The histopathological and immunohistochemical examinations of the injured infrapinatus muscle revealed tissue changes that indicated acute muscle rupture, without any signs of an initiating degenerative process. On the day following surgery the dog was fully weight bearing. Restriction of activity for four weeks was recommended. Eight months after the initial injury, the dog had completely recovered and had full days of vigorous exercise and hunting activity without any apparent lameness. The findings in this case suggested that the infraspinatus muscle may be considered to be an osteo-fascial compartment in dogs and must be added to the list of compartments that may pose a potential risk for OFCS in the canine extremity.
Keywords: Canine; compartment syndrome; infraspinatus muscle